Diabetes Self Management Education Sebagai Perawatan Mandiri Pasien Diabetes Melitus di Tengah Masa Pandemi COVID-19 Systematic Review - Masu, Vinsensius Idelfonsus Fence; Riwu, Magdarita; Kareri, Dyah Gita Rambu; Damanik, Efrisca M. Br. (Cendana Medical Journal, 2023)
Background: Diabetes self management education (DSME) is an ongoing process to improve the knowledge, skills and abilities needed for self-care of people with diabetes. Purpose: This Systematic review aims to analyze the role of diabetes self management education for patients with type 2 diabetes melitus in the midst of the Covid-19 pandemic. Method: a systematic review was conducted using a search method using 3 electronic databases, namely PubMed, Google Scholar and Science Direct. Search using keywords with the PICO method. Inclusion criteria The method used is using journals that are available full text, with the type of research being randomized controlled trials and randomized controlled trials quasi experiment both use Indonesian and English with the subject being a Type 2 diabetes melitus patient. The journal year used is limited to 2019-2021. Results: the results of a literature search on 3 electronic databases of 32 selected journals as samples of this systematic review. From 32 journals, a systematic review showed that Diabetes self management education (DSME) had a significant effect on glycemic control in the form of decreasing HbA1c levels, improving quality of life, self care behavior, self management, and self efficacy, as well as decreasing symptoms. depression and stress levels. Conclusion: systematic review in 32 journals concluded that diabetes self management education has a significant effect on glycemic control in the form of decreasing HbA1c levels, improving quality of life, self care behavior, self management and self efficacy, as well as decreasing symptoms of depression and stress levels.